Characterization of jamun (Syzygium cumini) juice fortified with nanoemulsified vitamin D3: In vitro and in vivo assessment of its nutraceutical value and anti-diabetic potential - Yasmeena Jan; Reem Binsuwaidan; Muneeb Malik; Mifftha Yaseen; Sayeed Ahmad; Nawaf Alshammari; Mohd Adnan; Syed Amir Ashraf; Bibhu Prasad Panda (Food Chemistry: X)
This study aimed to fortify Jamun (Syzygium cumini) juice with vitamin D3 to address vitamin D deficiency and boost health. A nanoemulsion of vitamin D3 was fabricated using a low-temperature (4–200C) sonication method and incorporated into the juice. The vitamin D fortified jamun juice (VDFJJ) exhibited a total polyphenol content of 14.37 mg GAE/mL, total flavonoids of 8.27 mg QE/mL, and 94.2 % antioxidant activity. It demonstrated antidiabetic potential, with IC50 values for α-amylase and α-glucosidase inhibition at 110 μg/mL and 134 μg/mL, respectively. Vitamin D3 showed 82 % release profile in simulated gastrointestinal fluids. After 4 weeks of VDFJJ intervention in vitamin D-deficient animal models, serum levels of 25-OHD, PTH, calcium, phosphorus, and ALP were significantly improved. Vitamin D3 demonstrated stability within the matrix, showing a slight reduction from 4000 IU to 2440 IU over a three-month period. This nanoemulsion approach effectively enhances the solubility and bioavailability of vitamin D3 in low-fat beverages like jamun juice, offering significant nutritional benefits and anti-diabetic properties.